Mechanical and thermal properties of bamboo fiber reinforced polypropylene/polylactic acid composites for 3D printing - Long, Haibo; Wu, Zhiqiang; Dong, Qianqian; Shen, Yuting; Zhou, Wuyi; Luo, Ying; Zhang, Chaoqun; Dong, Xianming (Polymer engineering and science, 2019)
In this article, a kind of degradable composite was prepared from bamboo fiber (BF), poly lactic acid (PLA), and polypropylene (PP). The mechanical and thermal properties were characterized by the universal testing machine, thermogravimetric analysis, differential scanning calorimetry. In order to improve the compability between BF and polymer matrix several modification on the surface of BF were explored and compared. Moreover, a compatibilizer (maleated PP) was applied to further increase compatibility between the fiber and matrix. It is found that the thermal stability of BF/PP/PLA composites decreased with the increase of maleated polypropylene (MAPP) content. When 5% MAPP was used the tensile strength, flexural strength, and impact strength of composites reached 33.73, 47.18 MPa, and 3.15 KJ/m2, with an increase by 13, 11.7, and 23.5%, respectively, compared with the composites without MAPP. The improvement of mechanical properties is attributed to the fact that irregular grooves and cracks induced by the modification of BF facilitate the infiltration of polymer into fiber due to the strong capillary effect. Furthermore, BF/PP/PLA composites are potential to be used in 3D printing. POLYM. ENG. SCI., 59:E247–E260, 2019. © 2018 Society of Plastics Engineers